Overview of national plan for NHS blood and transplant and hospitals to address blood shortage in the United Kingdom (Series 1): Emergency management framework - GUO Jin; GUO Yongjian; WANG Hongjie; WANG Yong (Zhongguo shuxue zazhi, 2025)
As a vital resource, blood directly impacts the life and health of patients and the continuity of medical care. Given that it can only be obtained through voluntary donations from blood donors, its supply is susceptible to shortages due to various external factors. As the first article in a series introducing the " National Plan for NHS Blood and Transplant and Hospitals to Address Blood Shortage in the United Kingdom", this paper provides a detailed overview of the UK’s emergency management system, with a particular focus on its health emergency management framework. Regarding the UK’s emergency management system, this article elaborates on the regulatory and standards framework and institutional mechanisms for emergency management, non-statutory guidance documents offering preparation and implementation advice, the local resilience forums (LRFs) system enabling cross-departmental and multi-agency emergency coordination and collaboration, the UK government’s capacity-building efforts, as well as emergency response entities and command-and-control mechanisms. Supplementing the preceding review, the article further details the legal basis of the UK’s health emergency system and the core standards framework of national health service (NHS) emergency preparedness, resilience, and response (EPRR), with specific reference to relevant documents.